Anemia management in chronic kidney disease and dialysis: a narrative review. Issue 3 (May 2017) - Collister, David; Rigatto, Claudio; Tangri, Navdeep
Abstract : Purpose of review: This review describes the current state of anemia management with erythropoietin (EPO)-stimulating agents and iron supplementation in both chronic kidney disease and dialysis patients, with a focus on novel therapies. Recent findings: We review the benefits and risks of EPO-stimulating agents, focusing on health-related quality of life and the uncertainties regarding optimal iron utilization in patients with kidney disease. We discuss novel therapies for iron supplementation including iron-based phosphate binders and dialysate iron delivery as well as alternatives to EPO-stimulating agents including hypoxia-inducible factor prolyl hydroxylase inhibitors. Summary: Individualization of hemoglobin targets using EPO-stimulating agents and iron supplementation may be considered in younger, healthier patients with kidney disease to improve health-related quality of life. Optimal iron utilization in kidney disease patients is unclear, but novel iron base phosphate binders and dialysate iron delivery may play a role in intravenous iron avoidance and its potential complications. Phase 3 randomized controlled trials of hypoxia-inducible factor prolyl hydroxylase inhibitors are ongoing and are promising new alternatives to EPO-stimulating agents and their known adverse effects.